Możliwości wykorzystania metod kartograficznych w gospodarczych systemach informatycznych - Stępniak, Cezary (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
A Geographic Information System is one of the modern computerized tools. The system is built on the base of cartographic methodology. Producers of GIS application can use all cartographic took Additionally they can use new possibilities, which are the results of information technology progress. GIS applications can be integrated with business information system (e.g. ERP applications). The integration can be realized on two levels: data and tools. The data level integration is based on possibilities of using the same databases by users of both kinds of system. The tools level uses cartographic tools for business processes description. On the second of mentioned level, GIS application can describe geographical reality or business processes, which can be presented by using heuristic tools. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 386-398